2002
DOI: 10.1590/s0074-02762002000500030
|View full text |Cite
|
Sign up to set email alerts
|

Influence of specific treatment on the morbidity of schistosomiasis mansoni in an endemic area of Minas Gerais, Brazil

Abstract: Key words: schistosomiasis mansoni -clinical evolution -morbidity -treatment -Minas Gerais -BrazilThe elevated prevalence and severity of Schistosoma mansoni infection in the area of Itanhomi, Minas Gerais, was first observed in 1972 in the Santa Luzia do Carneiro village, in a pilot sectional survey ). In 1973 a hyper endemic area was detected in Capitão Andrade, Vale do Rio Doce, Minas Gerais (Figure), with the splenomegaly index of 5.6%. The severity of the clinical forms in the present municipality of Capi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…In the last two decades, studies performed in Brazil [5] , [6] , [9] , [10] , [12] , [13] , [17] [19] , [32] , and in other countries [20] [27] , have described the distribution of infection, reasons and frequency of contact with natural waters, as well as other parameters related to schistosomiasis mansoni.…”
Section: Discussionmentioning
confidence: 99%
“…In the last two decades, studies performed in Brazil [5] , [6] , [9] , [10] , [12] , [13] , [17] [19] , [32] , and in other countries [20] [27] , have described the distribution of infection, reasons and frequency of contact with natural waters, as well as other parameters related to schistosomiasis mansoni.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the results from these campaigns could not be properly investigated, although such evaluations would have been extremely important for disease control efforts. In experimental field studies conducted on a smaller scale, Prata (1970, 1974) in Bahia, Katz et al (1977Katz et al ( , 1980 in Minas Gerais (MG) and Coura et al ( , 1984Coura et al ( , 1992, Conceição and Borges-Pereira (2002) and Conceição et al (2007) in other areas of MG have demonstrated the possibility of reducing the rates and intensities of infection among treated individuals who remained in the endemic area. Furthermore, they have shown a reduction in the progression of the disease to severe forms.…”
mentioning
confidence: 99%
“…Personal experience with specific treatment for schistosomiasis as a strategy for control -It has already been proven that large-scale specific treatment for schistosomiasis in endemic areas (excluding the cases with contraindications) can reduce the prevalence of infection over the short term, as well as the morbidity due to the disease over the medium and long term (Jansen 1946, Sette 1953, Rodrigues da Silva 1958, Kloetzel 1963, 1972, Bina & Prata 1974, Prata 1976, Katz et al 1977, 1992, Machado 1982, Conceição et al 2002, 2007. This advance can then be consolidated through repeated treatments (Coura 1995, Coura & Amaral 2004.…”
mentioning
confidence: 99%
“…Following the master’s degree dissertations and PhD thesis of Conceição (1976, 1985) in Capitão Andrade, MG, and of Mendonça (1982) in Alhan- dra, PB, several studies were conducted by Conceição and Borges-Pereira (2002), Conceição et al (2007) and Conceição and Coura (2012) on the prevalence of morbidity, evolution and the response to specific treatment of schistosomiasis in rural areas in MG. In PB, in addition to the study conducted by Mendonça (1982) in Alhandra, Coura et al (1987) conducted an evaluation of the Schistosomiasis Control Program in all areas covered by the program in that state, including Alhandra.…”
Section: Discussionmentioning
confidence: 99%